Mitochondrial respiratory chain deficiency in older men and its relationship with muscle mass and performance. Issue 2 (1st July 2017) - Rygiel, Karolina A; Dodds, Richard M; Patel, Harnish P; Syddall, Holly E; Westbury, Leo D; Granic, Antoneta; Cooper, Cyrus; Cliff, Joshua; Rocha, Mariana C; Turnbull, Doug M; Sayer, Avan A
Abstract: Introduction: Sarcopenia is the loss of muscle mass and physical performance with age, and recognition of its importance in clinical practice is growing. Age‐related decline in muscle mitochondrial function has been described although less is known about the role of mitochondrial dysfunction in sarcopenia. The aim of this study was to investigate whether respiratory chain deficiency is associated with muscle mass and physical performance among a sample of healthy older men participating in the Hertfordshire Sarcopenia Study. Methods: We used immunofluorescence on biopsies of the vastus lateralis to measure levels of the NDUFB8 subunit of complex I and the COX‐1 subunit of complex IV per fibre. We measured muscle mass using dual‐energy x‐ray absorptiometry. We assessed physical performance using grip strength, gait speed, chair rise time, timed up and go and standing balance time, and composed an aggregate performance score on the scale of 0 (worst) and 5 (best performance). We used linear regression with a cluster sandwich estimator to test relationships between complex I / IV and muscle mass / physical performance. Study approval was granted by the Hertfordshire Research Ethics Committee. Results: Samples were available from 77 participants of mean age 72.6 (2.5) years. The median number of fibres analysed per participant was 157 (104, 237). We expressed complex I and IV levels as Z‐scores relative to that expected in young controls. The overall participant mean Z‐scores were 0.3 (1.3) and ‐1.5 (0.9) for complex I and IV, respectively. We saw no relationship between complex I or IV and muscle mass. Each unit (SD) increase in complex I was associated with an increase in aggregate performance score of 0.06 (95% CI: 0.02, 0.09, P = 0.003), whilst the relationship for complex IV did not reach significance. Conclusion: We saw marked heterogeneity in complex I and IV levels, both between and within participants, as well as lower overall levels of complex IV. The finding of a small but statistically significant positive association between complex I levels and physical performance suggests that mitochondrial dysfunction may have a role in the development of sarcopenia. These findings will help inform the design of future studies across a wider range of ages and in both women and men.